School is no longer the temple of learning. (Journal of Parents and Teachers, 2025)
The article is based on the International Year of Adult Education, where education and culture are two interconnected terms, as education provides access to work, and culture represents leisure for adults. However, there is no age limit for education or culture, which is why it is essential to promote their union in learning and the concept of the "School without Walls" referenced by schools in the U.S.
Keywords: walls